EFEKTIVITAS TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KEPERCAYAAN DIRI - Ira Miranda; Ibrahim Al Hakim; Bangun Yoga Wibowo (Universitas Sultan Ageng Tirtayasa, 2019)
This Research was motivated by the problem low self-confidence at grade eight of Three Junior High School Kramatwatu 2019-2020 academic year. The aim of this research is to determine the profile of self-confidence and determine the effectiveness of role playing technique to improveself confidence at the eight grade students. Role playing technique used included group guidance. The type of research use pre-experimental design with one group pre-test post-test design. Population of this research is student grade eight with agestwelve to fourteen. Sample of this research is six student include of low self-confidence category with purposive sampling. This research use questionnaire has tested for content validity an there were 53 valid items out of the original 92 items. The results showed that the students' self-confidence profile obtained a 9% low category group percentage, 63% medium category, and 28% high category. The use of the effectiveness of role playing technique to improve student self-confidence was evidenced in the results of the t test, which was a significance value was lower than 5% (p = 0.01 < 0.05). Average in pre-test is 18.33 while in the post-test is 29.50 which mean there is an improvement in self-confidence at the grade eight of Three Junior High School Kramatwatu 2019-2020 academic year after given role playing technique.Keywords: Self-Confidence, Group Counseling, Role Playing Technique